Menara Putrajaya Holdings Sdn.Bhd. Wilayah Persekutuan Putrajaya / Muhamad Fauzi Hashim ... [et al.] - Hashim, Muhamad Fauzi; Zamaludin, Muhammad Azim; Khalid, Muhammad Hasif Hazman; Abdullah Thani, Nur Hanis; Kadis, Zarina (Universiti Teknologi Mara, Perak, 2016)
Putrajaya is Malaysia administrative capital. The root name of Putrajaya is Prang Besar. Putrajaya is well-planned city where all the construction has been planned before it become to reality. A company that has the responsibility to developt Putrajaya is Putajaya Holdings.Putrajaya Holdings was given task of translating the vision of Putrajaya into Reality. As master developer, Putrajaya Holdings is work to implement the master plan that made Putrajaya as a garden city and an intelligent city. Todays, more than half of the 4,931- hectare development has been completd. They are mainly governments building, housing, infrastructure, public utilities and amenities.